2020
DOI: 10.1166/jnn.2020.17407
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Spray-Drying and Freeze-Drying for the Production of Stable Silybin Nanosuspensions

Abstract: Spray-drying and freeze-drying are effective approaches to improve the long-term stability of nanosuspensions. This research explored the effect of spray-drying and freeze-drying techniques on PVP K30-stabilized silybin nanosuspensions. The morphology was observed by scanning electron microscopy (SEM): The spray-dried sample was spherical, and the freeze-dried samples were rodlike with smooth surfaces. The redispersibility was studied via dynamic light scattering (DLS): The size, PDI, and zeta of the spray-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In addition, the disadvantages of this process are inadequate drying, spoiling due to wind, rain, dust and moisture, the encroachment of insects, rodents and birds and fungal growth (Purohit et al, 2006;Sharma et al, 2009). Therefore, artificial drying systems are preferred for several reasons (Erbay and Küçüköner, 2008) When comparing drying methods, freeze-drying, also called lyophilization, is the best preservation method with the application of primary drying/ice sublimation and drying/desorption of unfrozen water (Ma et al, 2020). Additionally, sublimation processing under vacuum at low temperatures minimizes enzymatic and nonenzymatic browning reactions, biological activities, texture, aroma and nutritional values of foods (Dirim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the disadvantages of this process are inadequate drying, spoiling due to wind, rain, dust and moisture, the encroachment of insects, rodents and birds and fungal growth (Purohit et al, 2006;Sharma et al, 2009). Therefore, artificial drying systems are preferred for several reasons (Erbay and Küçüköner, 2008) When comparing drying methods, freeze-drying, also called lyophilization, is the best preservation method with the application of primary drying/ice sublimation and drying/desorption of unfrozen water (Ma et al, 2020). Additionally, sublimation processing under vacuum at low temperatures minimizes enzymatic and nonenzymatic browning reactions, biological activities, texture, aroma and nutritional values of foods (Dirim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…12 If a transformation from amorphous to crystallization occurs, the density of the microparticles will increase and the geometric particle size may also change, which in turn affects the aerodynamic particle size. 13 DSC results of SFD APIs showed that the microparticles had an exothermic peak for MF crystallization (►Fig. 3); however, the PXRD results showed no characteristic diffraction peaks (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cryochemical methods of synthesis and modification of drug nanoparticles are based on the combination of the processes of evaporation or sublimation of a drug substance by heating under vacuum conditions, followed by condensation of the drug molecular vapor at support surfaces cooled to cryogenic temperatures (77-100 K) [56,57] (Figure 7). Another powerful cryogenic technology is the spray freeze-drying technique of frozen water or mixed water-organic solutions of drug substances under vacuum conditions [56,[58][59][60][61][62][63][64][65] Supercritical technologies have been shown to reduce the particle size of Fenofibrate down to 1.8-8.33 µ m compared to untreated Fenofibrate (24.2 ± 0.8 µ m) [51]. Supercritical anti-solvent technology was utilized to reduce the particle size of Betamethasone [52], Myricetin [53], and Luteolin [54].…”
Section: Cryogenic Technologies (Cryogenic Freeze Drying Of Water Sol...mentioning
confidence: 99%
“…Cryochemical methods of synthesis and modification of drug nanoparticles are based on the combination of the processes of evaporation or sublimation of a drug substance by heating under vacuum conditions, followed by condensation of the drug molecular vapor at support surfaces cooled to cryogenic temperatures (77-100 K) [56,57] (Figure 7). Another powerful cryogenic technology is the spray freeze-drying technique of frozen water or mixed water-organic solutions of drug substances under vacuum conditions [56,[58][59][60][61][62][63][64][65] (Figure 8). The use of low temperatures enables the reduction in drug substance particles down to the nanoscale and stabilization of metastable crystal structures, allowing the creation of new polymorphic crystal modifications of known drug substances.…”
Section: Cryogenic Technologies (Cryogenic Freeze Drying Of Water Sol...mentioning
confidence: 99%